A Network Analysis of Gender Differences in PTSD Symptoms among Chinese Adults during COVID-19 Pandemic - Fan Yang; Xiaohan Liu; Bo Zhang; Mingqi Fu; Ning Huang; Cheng Zhen; Jing Guo (Mental Illness)
Background. The COVID-19 pandemic is by far the most significant public health crisis in the 21st century, arousing many psychological concerns like post-traumatic stress disorder (PTSD). Aims. This study is aimed at revealing gender differences and similarities in PTSD symptoms among Chinese adults during COVID-19 pandemic. Methods. Data used in this study were from an online cross-sectional study conducted in February 2020 via a web-based platform. We analyzed data from 558 Chinese adults (334 men and 224 women) with PCL-5 scores over the PTSD criteria. A network analysis was performed to explore the structure of PTSD symptoms for subgroups of men and women. Results. The results showed intrusive thoughts and emotional cue reactivity, together with negative beliefs and negative trauma-related emotions, presented strong positive connections in both men and women. A negative connection between intrusive thoughts and self-destructive/reckless behavior existed among women but not men. Regarding centrality symptoms, women and men had flashbacks and self-destructive/reckless behavior in common, but with differential orders. The most central symptom of PTSD was self-destructive/reckless behavior for women and difficulty concentrating for men. Conclusion. We urge that self-destructive/reckless behaviors and flashbacks, as potential core symptoms of COVID-19-related PTSD, be given more attention in future pandemic-related psychiatric intervention programs.